A Dynamic Spatial Model of Rural-Urban Transformation with Public Goods - Biller, Dan; Andres, Luis; Cuberes, David (World Bank Group, Washington, DC, 2014)
This paper develops a dynamic model that explains the pattern of population and production allocation in an economy with an urban location and a rural one. Agglomeration economies make urban dwellers benefit from a larger population living in the city and urban firms become more productive when they operate in locations with a larger labor force. However, congestion costs associated with a too large population size limit the process of urban-rural transformation. Firms in the urban location also benefit from a public good that enhances their productivity. The model predicts that in the competitive equilibrium the urban location is inefficiently small because households fail to internalize the agglomeration economies and the positive effect of public goods in urban production.